Responsivitas Dan Transparansi Pemerintah Kota Yogyakarta Dalam Menangani Keluhan - Try Syeftiani; Mar Atun Saadah (UIR Press, 2023)
The purpose of this study is to discuss the responsiveness and transparency of the Yogyakarta City government in handling complaints in the 2013-2019 period. This study uses the theory of responsiveness and transparency in the delivery of public services. The research method used is qualitative with a case study approach. The results of the study show that the responsiveness and transparency of the Yogyakarta City government in handling complaints has not been maximized. In terms of responsiveness, it is indicated by the existence of complaints that have not been followed up by the government and the discovery of complaints that have the wrong destination (wrong address). Then, the Yogyakarta City government also has not created effective communication to coordinate resolving complaints involving several agencies/SKPD. Meanwhile, from a transparency standpoint, the Yogyakarta City government does not provide indicators of complaints that can be followed up by the Yogyakarta City Government. So that this causes the community not to know the criteria for complaints that can be followed up by the Yogyakarta City government.